Analisis Pengembangan Desa Wisata Melalui Komponen 4A di Desa Wisata Batulayang, Bogor - Nathaliu, Helen; Rosanto, Stephanie (Business and Investment Review, 2024)
Batulayang Tourism Village officially became a Tourism Village in 2014. This village often wins awards with nominations as a Sustainable Tourism Village. However, there is a lot of infrastructure that must be developed, namely public facilities and road conditions. The aim of this research is to analyze the 4A components (Attraction, Amenities, Accessibility, and Ancillary services) especially accessibility in the Batulayang Tourism Village. The research method used is descriptive qualitative with a case study approach. The analysis method used is SWOT Analysis and SWOT Matrix. The type of data collection technique uses the triangulation method, namely observation, interviews and documentation. The results of this research show that several 4A components are not optimal, such as accessibility and ancillary services. The results of the SWOT matrix carried out show that the Batulayang Tourism Village needs to develop through the 4A components.